(untitled) (Marketing Journal, 2025)
Improving the practice of providing settlement services to commercial banks for the foreign trade activities of business entities allows for timely receipt of export earnings and timely payment for imports of business entities. In particular, documentary l etters of credit fully guarantee payment for the amount of exported goods. On the contrary, payment is not guaranteed in bank transfers at all. The article identifies current problems related to improving the practice of providing settlement services to commercial banks for the foreign trade activities of business entities and develops scientific proposals aimed at solving these problems.